Bersatu dalam Perbedaan: Membangun Toleransi Beragama untuk Perdamaian - Islami, Muhammad Shokhikhul (Maliki Interdisciplinary Journal, 2025)
It is very important to build religious tolerance in society as a foundation for building a happy and peaceful community. Although there are several challenges such as prejudice, the negative impact of social media, and a lack of tolerance education, there are several strategies that can be implemented such as increasing multicultural education, encouraging interfaith dialogue, involving religious leaders, and conducting campaigns to increase public awareness. To ensure that future generations can coexist peacefully in diversity, practical and sustainable steps must be implemented by all elements of society.